Design of a dual‐band patch antenna with circular parasitic elements for adaptive polarization adjustment. Issue 11 (November 2016) - Yoo, S. J.; Choo, H.; Byun, G.
ABSTRACT: This letter proposes the design of microstrip patch antennas for independent polarization adjustments in two frequency bands. The proposed antenna consists of two radiating patches for dual‐band operation, and each patch is composed of a circular resonator and surrounding parasitic elements. The antenna polarization is adaptively adjusted by rotating these parasitic elements for each patch without changing other design parameters. As an evaluation, two sample antennas with linear and circular polarizations are fabricated to measure their radiation characteristics. The results prove that the proposed structure is capable of independent polarization adjustments for dual‐band operations. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2643–2649, 2016